Etiology and Outcome of Acute Kidney Injury in Children - Duzova, Ali; Bakkaloglu, Aysin; Kalyoncu, Mukaddes; Poyrazoglu, Hakan; Delibas, Ali; Ozkaya, Ozan; Sonmez, Ferah (Springer, 2010)
The aim of this prospective, multicenter study was to define the etiology and clinical features of acute kidney injury (AKI) in a pediatric patient cohort and to determine prognostic factors. Pediatric-modified RIFLE (pRIFLE) criteria were used to classify AKI. The patient cohort comprised 472 pediatric patients (264 males, 208 females), of whom 32.6% were newborns (median age 3 days, range 1-24 days), and 67.4% were children aged > 1 month (median 2.99 years, range 1 month-18 years). The most common medical conditions were prematurity (42.2%) and congenital heart disease (CHD, 11.7%) in newborns, and malignancy (12.9%) and CHD (12.3%) in children aged > 1 month. Hypoxic/ischemic injury and sepsis were the leading causes of AKI in both age groups. Dialysis was performed in 30.3% of newborns and 33.6% of children aged > 1 month. Mortality was higher in the newborns (42.6 vs. 27.9%; p < 0.005). Stepwise multiple regression analysis revealed the major independent risk factors to be mechanical ventilation [relative risk (RR) 17.31, 95% confidence interval (95% CI) 4.88-61.42], hypervolemia (RR 12.90, 95% CI 1.97-84.37), CHD (RR 9.85, 95% CI 2.08-46.60), and metabolic acidosis (RR 7.64, 95% CI 2.90-20.15) in newborns and mechanical ventilation (RR 8.73, 95% CI 3.95-19.29), hypoxia (RR 5.35, 95% CI 2.26-12.67), and intrinsic AKI (RR 4.91, 95% CI 2.04-11.78) in children aged > 1 month.
Keywords: Epidemiology; Mortality; pRIFLE; Prognosis